2002
DOI: 10.1096/fj.01-0816fje
|View full text |Cite
|
Sign up to set email alerts
|

Phytanic acid, a natural peroxisome proliferator‐activated receptor agonist, regulates glucose metabolism in rat primary hepatocytes

Abstract: Phytanic acid, a metabolite of the chlorophyll molecule, is part of the human diet and is present in normal human serum at low micromolar concentrations. It was previously shown to be a ligand of the 9-cis-retinoic acid receptor and peroxisome proliferator-activated receptor (PPAR) a. PPAR agonists are widely used in the treatment of type 2 diabetes. Here, we report that phytanic acid is not only a transactivator of PPARa, but it also acts via PPARb and PPARg in CV-1 cells that have been cotransfected with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
81
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(85 citation statements)
references
References 39 publications
4
81
0
Order By: Relevance
“…The subcellular localization of IDH1 in both cytosol and peroxisomes ideally situates it to respond to the lipogenic requirement of the cell. The coproduct of the reaction, ␣-ketoglutarate, which is required as a cosubstrate for the phytanoyl-CoA ␣-hydroxylase reaction (17)(18)(19)(20), is required for the catabolic removal of phytanic acid, a known agonist to PPAR␣ (21,22). PPAR␣ is highly expressed in heart, muscle, kidney, and endothelial cells, but mostly in liver (27,34), where its function is in the catabolism of fatty acids through the regulation of genes encoding mitochondrial and peroxisomal enzymes important for ␤-oxidation (68).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The subcellular localization of IDH1 in both cytosol and peroxisomes ideally situates it to respond to the lipogenic requirement of the cell. The coproduct of the reaction, ␣-ketoglutarate, which is required as a cosubstrate for the phytanoyl-CoA ␣-hydroxylase reaction (17)(18)(19)(20), is required for the catabolic removal of phytanic acid, a known agonist to PPAR␣ (21,22). PPAR␣ is highly expressed in heart, muscle, kidney, and endothelial cells, but mostly in liver (27,34), where its function is in the catabolism of fatty acids through the regulation of genes encoding mitochondrial and peroxisomal enzymes important for ␤-oxidation (68).…”
Section: Discussionmentioning
confidence: 99%
“…Several metabolic functions for phytanic acid have been reported: regulation of glucose metabolism in primary rat hepatocytes by acting as an agonist to peroxisome proliferator-activated receptors (PPARs) (21,22) and retinoid X receptor (RXR) (23); white adipocyte differentiation (24); and activation of uncoupling protein-1 gene transcription and brown adipocyte differentiation (25). In the autosomal disorder Refsum's disease, ␣ -oxidation of phytanic acid is affected in some, but not all, cases, and accumulation of this acid is observed in various tissues (26).…”
mentioning
confidence: 99%
“…A number of PPARs activators that are of food/diet origin have been identified. Conjugated linoleic acids [25] and phytanic acid [12] are well-known examples of which health benefits have been demonstrated. The hypolipidemic effect of fish oil [8] has been attributed, at least in part, to the activation of PPARa.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study showed that phytanic acid had cytotoxic effects on the mitochondria and stellate cells in the rat brain (Schönfeld et al, 2006). However, both phytanic and pristane acids play a regulatory role in adipocyte differentiation and polyester, glucose, and lipid metabolism (Heim, 2002); it can promote fatty acid b-oxidation and significantly lower liver triglyceride and plasma fatty acids (Gloerich et al, 2007). In this study, both commercial pellet feed-feeding and small trash fish-feeding crabs contained high levels of phytanic acid, suggesting that crab is similar to other high phytanic acid foods and may have potential health functions.…”
Section: Phytanic Acidmentioning
confidence: 98%